Diversity ASX corporate governance recommendations: a step towards change?. Issue 3 (3rd July 2017) - Shimeld, Sonia; Williams, Belinda; Shimeld, Justin
Abstract : Purpose: The business case argument was used to underpin the inclusion of diversity disclosures within the Australian Securities Exchange (ASX) Corporate Governance Principles and Recommendations (2010). By adding a requirement for diversity disclosure, an increase in focus on diversity would be expected because of a heightened level of accountability. Whether this change in the Recommendations affected any change in the boardroom is questionable though. The purpose of this paper is to explore the effectiveness of these disclosure requirements. Design/methodology/approach: The authors draw on data obtained from a random sample of 120 ASX-listed company annual reports across two time periods: 2009 and 2012 (before and after the change in the Recommendations). Findings: Although findings indicate that there has been some change, especially in the more visible companies (ASX200), many of the changes appear to be largely superficial with a continued focus on the business case perspective. Social implications: While the disclosure recommendations have the potential to be a driver in addressing gender inequity, the findings of this paper indicate that without deep change at the organisational level, requiring listed companies to disclose on gender diversity may have little impact, with the focus remaining on the business case and business as normal. Originality/value: This paper contributes to the literature on gender diversity in the boardroom and the effect of disclosure. The empirical findings contribute to an understanding of the diversity Recommendations within the ASX Corporate Governance Principles and Recommendations, but in doing so, it calls for deeper organisational cultural change if real change is to take effect.